A Literary Review on the Role of Arjuna in Ayurveda - Naskar, Prabir; Pan, Aniruddha (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Arjuna (Terminalia arjuna Roxb., family Combretaceae), is the most accepted and beneficial medicinal plant in the traditional system of medicine for the treatment of various critical diseases and disorders and commonly found in Asian countries. Therefore, the detailed literature review of Arjuna and its formulations mentioned in Ayurvedic classics is crucial in present era. Aim: The aim of this study was to evaluate the therapeutic potential of Arjuna by assimilating ancient and modern medical knowledge. Materials and Methods: All information is collected from various classical Ayurvedic text books including Samhitas and Nighantus as well as various other literatures and publications. Results and Discussion: Different literatures revealed that this plant has numerous health benefits and traditionally used in the treatment of various diseases. From different studies, we found that different parts of T. arjuna contain numerous phytoconstituents (such as alicyclic acid, amino acids, polypols, arjunglucoside I, II and III, ellagic acid, arjunic acid, and tannic acid) and have anti-oxidant, cardioprotective, anti-inflammatory, anti-mutagenic, anti-cancer, and anti-atherogenic effects. Conclusion: As we got detail information regarding Arjuna form various classical literatures, we can come into conclusion that Arjuna is one of the most effective drug use to treat various different human disorders, which is also supported by various modern literatures based on research.